2020
DOI: 10.32598/ptj.10.1.430.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Muscle Strength and Range of Motion in Lower Extremity With Balance and Risk of Falling in Elderl

Abstract: Purpose: The present study examined the relationship between muscle strength and range of motion in lower extremity with balance and risk of falling in the elderly. Methods: This was a cross-sectional study. The statistical population included healthy elderly (Mean±SD age: 65.64±4.95 y) in Rasht City, Iran. The study was conducted on 65 healthy elderly males who met the study inclusion criteria and were selected by convenience sampling method. In this study, to measure static and dynamic balance, Sharpened Rom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Although there were significant differences in FIM-M, knee extension muscle strength, Frail CS-10, SLS, and TUG between the two groups, each of these measures alone was not a determinant of whether a walking aid was to be used. As balance function correlates with knee extension muscle strength in the elderly [ 41 ], we speculated that the walking aid group had impaired balance function due to diminished knee extension muscle strength and used walking aids to compensate for compromised balance. In addition, previous studies have shown that decreased knee extension muscle strength affected walking stability [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were significant differences in FIM-M, knee extension muscle strength, Frail CS-10, SLS, and TUG between the two groups, each of these measures alone was not a determinant of whether a walking aid was to be used. As balance function correlates with knee extension muscle strength in the elderly [ 41 ], we speculated that the walking aid group had impaired balance function due to diminished knee extension muscle strength and used walking aids to compensate for compromised balance. In addition, previous studies have shown that decreased knee extension muscle strength affected walking stability [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that both a sedentary lifestyle and low physical activity levels have a significant impact on postural parameters [ 37 ]. It appears that engaging in physical activity can enhance body condition through the improvement of muscle strength, balance, flexibility, and range of motion [ 38 ]. Additionally, a healthier lifestyle in women is associated with increased awareness, motivation and commitment to ERBE.…”
Section: Discussionmentioning
confidence: 99%
“…27 will reducing dynamic balance and the risk of falling in the elderly. 8 Another study conducted by Asti et al (2017) found that respondents with good moderate muscle strength had a low risk of falling, and no elderly with moderate muscle strength had a high risk of falling. In other words, this study shows a relationship between muscle strength and the risk of falling in the elderly caused by balance disorders.…”
Section: Original Articlementioning
confidence: 98%
“…There was also a significant relationship between ankle dorsiflexion muscle strength with dynamic balance and risk of falling (p≤0.05). 8 This is because balance is a complex movement skill that describes postural dynamics in preventing falls. 25 Postural control and balance is a function of the interaction between the nervous and musculoskeletal systems.…”
Section: The Relationship Between Leg Muscle Strength and Dynamic Bal...mentioning
confidence: 99%
See 1 more Smart Citation